Final surface modification for better wear resistance of ceramic coating on cast AlSi10Mg alloy. Issue 24 (15th December 2022) - Gabor, Roman; Prymus, Tomáš; Cvrček, Ladislav; Nehasil, Václav; Hlinka, Josef; Buřil, Matěj; Tokarčíková, Michaela; Seidlerová, Jana
Abstract: Using the design of experiment (DOE) method and the micro-arc oxidation (MAO) technique, ceramic layers on AlSi10Mg alloy were systematically prepared to design optimal process conditions for achieving the best tribological properties of the ceramic layers. The lowest concentrations of the applied 6 g/l NaOH and 12 g/l Na2 SiO3 resulted in the preparation of uniform MAO layers with the lowest rated parameters Ra, Rz and thickness achieved under micro-arc discharge conditions at 500 V and 60 min. With the increasing thickness of the coatings, there was an increase of Si in the MAO coating. Full factorial DOE was used to optimize the tribological properties in a polyalphaolefin (PAO) environment at 80 °C. The most significant influence for the preparation of abrasion-resistant layers for the investigated factors was identified on the AlSi10Mg alloy by the NaOH content in the electrolyte. The friction coefficients of MAO coatings reached an average value of 0.15. Aero-lap polishing technology was applied for increased wear resistance requirements to eliminate the deficiencies of MAO coatings, leading to decrease wear track by almost double compared to polished silumin. Removal of the outer MAO layer by polishing led to a reduction in the high corrosion resistance of the MAO coating, demonstrating the influence of the outer layer not only on the tribological properties but also on the corrosion resistance of MAO coatings.